What brings intentions to mind? An in situ study of prospective memory - Sellen, Abigail; Louie, G.; Harris, J. E.; Wilkins, A. J. (Memory, 1997)
In a naturalistic study, we aimed to uncover the relationship between thinking about and remembering intentions.